Filter System Designed to Reduce The Emission of Gasoline Motorcycle Pollutants - Pinem, Mekro Permana; Yusuf, Yusvardi; Wardana, Muhammad Bayu; Caturwati, Ni Ketut; Listijorini, Erny; Satria, Dhimas; Sukamto, Dwinanto (Machine : Jurnal Teknik Mesin, 2025)
Clean and healthy air are major topics around the globe. It is because poor air quality hurts human health and is even responsible for the deaths of millions of people. This work develops exhaust pipes containing filters to reduce the pollutants emitted by motorcycles. There are three pollutant concentrations measured here: CO2, CO, and HC. The measurements were taken before and after the filter system so that the pollutant reduction could be calculated.  The maximum pollutant reduction of the filter system: 6.1 % of CO2, 8.0 % of CO, and 651.0 ppm of HC. The primary mechanism of this filter is the physical trapping of pollutants. When the gas flows through the exhaust pipe, the pollutants in the stream are attached to the filter due to direct contact. This change can be visually observed in the filter color, which darkens after use in the exhaust pipe. However, a limitation of this work is its short-term experiment, which lasted only five minutes, indicating a key area for future research. It is also necessary to have alternative filters that are sustainable and can work properly in high-temperature conditions.